A reconfiguração do jornalismo visual nas interfaces digitais sob influência do design responsivo e da imprensa nativa da web - Araújo, Ricardo da Silva (2019)
The migration of the traditional press to the digital interfaces of the web has transformed the aesthetic representation of visual journalism. This is especially noticeable when the newsprint of printed newspaper covers is reproduced on homepages. Currently, the visual structures of digital newspapers are being developed exclusively for mobile users, presenting interfaces with responsive design resulting from advanced technology that enables web pages to adapt to any screen resolution on mobile devices. The result of the expressive use of this technology in websites and journalistic applications has limited the use of visual elements that have a visual impact on the news and the design of the pages, as in the covers of the printed matter. Based on the content analysis of 60 printed interfaces and 90 digital interfaces of O Estado de S. Paulo, O Globo and Nexo (digital native newspapers), based on the perception and editorial design, the study investigated how these aesthetic transformations can affect the language of visual perception of the news, how they change the way news is read, and how the traditional press has lost the visual identity of its printed pages in web environments.